Bifunctional Composites for Biofilms Modulation on Cervical Restorations. (September 2021) - Balhaddad, A.A.; Garcia, I.M.; Mokeem, L.; Ibrahim, M.S.; Collares, F.M.; Weir, M.D.; Xu, H.H.K.; Melo, M.A.S.
Cervical composites treating root carious and noncarious cervical lesions usually extend subgingivally. The subgingival margins of composites present poor plaque control, enhanced biofilm accumulation, and cause gingival irritation. A potential material to restore such lesions should combine agents that interfere with bacterial biofilm development and respond to acidic conditions. Here, we explore the use of new bioresponsive bifunctional dental composites against mature microcosm biofilms derived from subgingival plaque samples. The designed formulations contain 2 bioactive agents: dimethylaminohexadecyl methacrylate (DMAHDM) at 3 to 5 wt.% and 20 wt.% nanosized amorphous calcium phosphate (NACP) in a base resin. Composites with no DMAHDM and NACP were used as controls. The newly formulated 5% DMAHDM–20% NACP composite was analyzed by micro-Raman spectroscopy and transmission electron microscopy. The wettability and surface-free energy were also assessed. The inhibitory effect on the in vitro biofilm growth and the 16S rRNA gene sequencing of survival bacterial colonies derived from the composites were analyzed. Whole-biofilm metabolic activity, polysaccharide production, and live/dead images of the biofilm grown over the composites complement the microbiological assays. Overall, the designed formulations had higher contact angles with water and lower surface-free energy compared to the commercial control. The DMAHDM-NACP composites significantly inhibited the growth of total microorganisms, Porphyromonas gingivalis, Prevotella intermedia/nigrescens, Aggregatibacter actinomycetemcomitans, and Fusobacterium nucleatum by 3 to 5-log ( P < 0.001). For the colony isolates from control composites, the composition was typically dominated by the genera Veillonella, Fusobacterium, Streptococcus, Eikenella, and Leptotrichia, while Fusobacterium and Veillonella dominated the 5% DMAHDM–20% NACP composites. The DMAHDM-NACP composites contributed to over 80% of reduction in metabolic and polysaccharide activity. The suppression effect on plaque biofilms suggested that DMAHDM-NACP composites might be used as a bioactive material for cervical restorations. These results may propose an exciting path to prevent biofilm growth and improve dental composite restorations' life span.